Inside/Outside Nietzsche : Psychoanalytic Explorations - Wolfenstein, E. Victor (Book collections on Project MUSE., 2000)
"Eugene Victor Wolfenstein, a distinguished social theorist and practicing psychoanalyst, focuses on the opposition between the principles of psychoanalytic theory and Nietzsche's concepts of the will to power and perspectivism. Through critical engagement with these Nietzschean concepts, Wolfenstein brings them into the purview of psychoanalytic theory and practice." "Using this revised version of psychoanalytic theory, Wolfenstein then conducts a psychobiography of Nietzsche. He contends that Nietzsche philosophized from within a transitional space between the maternal and paternal extremes of the male imaginary, a space in which gender identity is notably unstable, and sublimity consorts with the most abject misery. This psychic location is the impetus for Nietzsche's conceptions of eternal return and the feminine." "Finally, Wolfenstein explores Nietzsche's genealogy of morals from a psychoanalytic perspective and in the light of Nietzsche's psychobiography. He concludes that Nietzsche's revaluation of values leaves us painfully short on both love and compassion." "The book is also framed by a critical engagement with Michael Foucault's problematics of power/knowledge."--Jacket.